Depression From a Precision Mental Health Perspective: Utilizing Personalized Conceptualizations to Guide Personalized Treatments - Deif, Reem; Salama, Mohamed (Frontiers in Psychiatry, 2021)
Modern mental health research and practice have proven that the “typical patient” requiring a standardized treatment does not exist, which presents the need for more personalized approaches to treatment targeting symptomatic profiles of individuals rather than broad and rigid diagnoses. In this regard, precision mental health has emerged focusing on enhancing prevention, diagnosis, and treatment of psychiatric disorders through identifying clinical subgroups, suggesting personalized evidence-based interventions, assessing the effectiveness of different interventions and identifying risk and protective factors for remission, relapse and vulnerability. Recently, there have been more active movements towards personalizing mental health on both the research and practice levels. The aim of this review is to provide an overview of reported findings in the conceptualization and treatment of depression from a precision mental health perspective. Different etiologies underlying depression have been theorized and different factors have been identified including neural circuitry, biotypes, psychosocial markers, biomarkers, genetics, and metabolomics. Each of these fields aim to explain individual differences on the pathological and therapeutic levels. One major aspect of treatment is the informed choice of the antidepressant drug which is ideally guided by research as indicated in medical guidelines. The precision approach may enhance this process as shown in a model involving the specification of depressive subtype based on symptomatic profiles. Despite all the advances in research, several challenges may still limit its clinical utility reflecting the need for translational research and empirical evidence to support a multidisciplinary approach towards the personalization of mental health care.